SINTESIS BIODIESELDARI MINYAK JELANTAHMENGGUNAKAN KATALIS BASA HETEROGEN BERBAHAN DASAR CANGKANG TELUR AYAM - Dalimunthe, Imam S.; Restuhadi, Fajar '; Efendi, Raswen ' (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2016)
Conducted research of biodiesel methyl ester of wastecooking oil and methanol with use of ash as a catalyst. This study was done to optimize the manufacture of biodiesel from used cooking oil. This study uses a completely randomized design with four treatments, T1 (Reaction tansesterifikasi 2 hours), T2 (transesterification reaction 3 hours), T3 (transesterification reaction 4 hours) and T4 (transesterification reaction 5 hours) with three replications. The data were analyzed using ANOVA, continued by DNMRT at 5% level. The results showed that the transesterification reaction time was significantly (P<0.05) influenced the acid number, total glycerol, viscosity, flash point and levels of methyl ester, but did not significantly affect (P>0.05) on the water content. The analysis has been carrried obtained the best treatment is T4 with the results said saponification (114,223 mg KOH/g), the acid value (0,495 mg KOH/g), total glycerol (0.137%), viscosity (3.376 cSt ), water content (0.002%), flash point (195.750Â°C) and the level of methyl ester (99.738%). Keywords: Biodiesel, waste cooking oil, catalyst transesterification reaction.